Left posterior fascicular block, state-of-the-art review: A 2018 update - Andrés Ricardo Pérez-Riera; Raimundo Barbosa-Barros; Rodrigo Daminello-Raimundo; Luiz Carlos de Abreu; Joseane Elza Tonussi Mendes; Kjell Nikus (Indian Pacing and Electrophysiology Journal, 2018)
We conducted a review of the literature regarding epidemiology, clinical, electrocardiographic and vectorcardiographic aspects, classification, and differential diagnosis of left posterior fascicular block.Isolated left posterior fascicular block (LPFB) is an extremely rare finding both in the general population and in specific patient groups. In isolated LPFB 20% of the vectorcardiographic (VCG) QRS loop is located in the right inferior quadrant and when associated with right bundle branch block (RBBB) ≥40%.The diagnosis of LPFB should always consider the clinical aspects, because a definite diagnosis cannot be made in the presence of right ventricular hypertrophy (RVH) (chronic obstructive pulmonary disease (COPD)/emphysema), extensive lateral myocardial infarction (MI) or extremely vertical heart.Intermittent LPFBs are never complete blocks (transient or second degree LPFB) and even in the permanent ones, one cannot be sure that they are complete. When LPFB is associated with RBBB and acute inferior MI, PR interval prolongation is very frequent. Keywords: Left posterior fascicular block, Bifascicular block, Intraventricular conduction disturbances